TINDAK TUTUR DIREKTIF DALAM DIALOG TOKOH FILM PENDEK JAWA BRAMBANG APUS - Gones Sekaring Puri; Harsono; R. Adi Deswijaya; Tri Widiatmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study motivated by the importance of speech acts in language use during social interactions, particularty theough directive speech acts in conversation. The javanese film Brambang Apus by Paniradya Kaistimewan contains various speech acts that reflect social values in Javanes culture. This study aims to describe the form and function of directive speech acts in the dialogue of the film`s characters. The method used is qualitative descriptive with literature study. The research data consists of utterances between characters in the film Brambang Apus. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study snow six types of speech acts, namely 1) Requests with the functions of asking, praying, and inviting. 2) Questions with the functions of asking interroganting. 3) Commands with the funtions of demanding, directing, and instructing. 4) Phohibitions with the functions of forbidding and restricting, and instructing. 5) Permission with the function of allowing. 6) Advice with the functions of counseling and giving guidance.